Expect the Unexpected: Unusual Neurological Presentation of Bone Marrow Sarcoidosis - Alahdab, Fares (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Bone marrow granulomas are rare and, when they occur, sarcoidosis is an uncommon etiology. This report describes a case of a 58-year-old man who presented with a five-month history of bilateral lower limb paresis. His paresis was associated with urinary and fecal incontinence and impotence, but without any loss of sensations. Head, chest, abdominal, and pelvic CT scans and MRI images, and a full-body Gallium 67 scan were all within normal limits. A CT-guided biopsy of the L1-L2 vertebral bodies showed non-caseating granulomatous inflammation. Serum angiotensin-converting enzyme (ACE) level was elevated. A diagnosis of bone marrow sarcoidosis was made after other differential diagnoses were excluded.